Prioritas pengembangan potensi pariwisata Distrik Sidey Kabupaten Manokwari berdasarkan pelaku dan alternatif pariwisata - Raharjo, Syafrudin; Aryanti, Metaleisya; Atmodjo, Ery (Cassowary, 2024)
ABSTRACT: Sidey District has the potential to become a West Papuan tourism icon. Sidey needs to prioritize the development of the tourism industry to guide future development planning. The objective of this study is to identify the key priorities for enhancing the tourism potential in Sidey District. The priorities are segmented into three categories: priority development criteria, priorities concerning tourism actors, and priorities related to tourism alternatives. The descriptive approach is used, and the analytical hierarchy process (AHP) facilitates decision-making. The collection of data involved conducting interviews with 7 experts, including academics, local community representatives, and regional government officials, using a questionnaire. Analysis of the questionnaire processing revealed a consistency value below 0.1, indicating that the weighting is deemed acceptable. According to the study, sidey's tourist potential may be divided into three categories: eco-edutourism, agro-edutourism, and build tourism. According to the findings of the AHP calculations, the allocation tourism development budget (35%) and institutional solid support (27%) were the two most important development criteria. The local government (34%) and the community (24%) are significant tourism actors. Eco-edutourism (48%) and agro-edutourism (40%) are the main alternatives to tourism growth. The alternative development follows the Manokwari Regency RIPPARDA's preferred course of action.